Digital Marketing and Creative Economy Theory in Economic Development during the Pandemic - Shin, Hsu Yu; Mynt, May Shun (Journal of Asian Multicultural Research for Economy and Management Study, 2021)
Changes in the world require a company to make innovations that are necessary in order to survive the onslaught of other companies' innovations, especially similar companies. a new economic concept that focuses on information and creativity that relies on creative ideas and knowledge from human resources for the main production factors. Creative economynowadays it is increasingly being carried out by the people, especially the younger generation in country because they feel this is a profession that is suitable to be done. Information technology is also needed in the distribution, promotion and sales transaction processes so that the process runs more effectively and efficiently. The potential for the development of this industry is due to several factors, namely the development of information technology as the main factor develops rapidly, access to information centers via the internet is much easier, the social innovation process runs smoothly, each region has a unique local cultural potential and the openness of society to modern culture, there are sources of knowledge such as many campuses that are a source of quality human resources, have high creativity and innovation.